A Finnish-Australian Acquisition: Organisational Problems and Issues - McMullen, I.; Soontiens, Werner (2004)
Although acquisitions are a popular way of internationalisation, the integration of acquired companies remains an arduous process that often impacts on the performance of the subsidiary or the overall organisation. Difficulties associated with integration mostly relate to cultural differences, either national or organisational. This paper reflects on the experience of Finnish and Australian staff involved in the acquisition of an Australian company by a Finish company. The paper points at problems and issues with business planning, vision sharing, effective management and leadership, cultural differences, cultural change, trust relationships and the integration environment as derived from literature and confirmed in the experience of interviewed respondents. The findings drawn from the case imply that it is imperative to avoid an 'us vs. them' atmosphere while both management and leadership must be strong and unbiased. Although a level of independence and identity should be allowed after the acquisition, integration of organisational cultures remains crucial for success.